How Does Religious Pluralism Affect Islamic Education in a Multicultural Society? - Wargo Wargo; Anjum Ahmed; Ansori Ansori (Zabags International Journal of Islamic Studies, 2024)
In order to meet the problems of religious diversity and foster unity in a multicultural society, this study aims to investigate successful Islamic religious education methodologies. By gathering information from a variety of textual sources, including books, scientific journals, articles, research reports, and other trustworthy sources that are pertinent to the research topic, the research methodology employed is library research. According to the study's findings and conclusions, it's critical to create inclusive curricula and teaching strategies, bolster digital literacy, instill moderate values, work with other educational institutions, incorporate universal values like justice and humanity, and enhance teachers' multicultural competency. Another crucial component of Islamic religious education is sensitivity to gender and equality issues. In a multicultural culture, this strategy can aid in fostering an accepting and tolerant perspective. To put these techniques into practice, it is suggested that support from the government and educational institutions be obtained. The cultivation of multicultural competence and training for Islamic religious education instructors is of utmost importance